KONTRIBUSI USAHATANI KELAPA TERHADAP PENDAPATAN KELUARGA DI DESA KLABAT KECAMATAN DIMEMBE KABUPATEN MINAHASA UTARA - Nofhita ., Mamentiwalo; Gene Henfried Meyer Kapantow; Elsje Pauline Manginsela (Sam Ratulangi University, 2019)
This study aims to find out: 1) The amount of average income of coconut farmers per quarter, 2) The amount of contribution of coconut farming to family income per quarter. Data collection in this study was conducted from October to November 2018 in Klabat Village, Dimembe District, North Minahasa Regency. The method used is the survey method, using primary data and secondary data. Primary data was obtained through direct interviews with 25 coconut farmers and one person from the Klabat Village based on a list of questions that had been prepared previously. Secondary data in this study were sourced from local bookstores, and the internet through Google Scholar to access articles from various scientificjournals and theses from Sam Ratulangi University and other universities related to the contribution of coconut farming to family income. The data obtained were analyzed using contribution analysis and using descriptive analysis presented in table form. The results showed that the amount of income received by coconut farmers was Rp. 1,837,320. While the contribution of coconut farming to household income is 27.45%. This means that coconut farming provides a moderate contribution and cannot be used as the main source of household income in Klabat Village.*eprm*